2012
DOI: 10.1159/000334098
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Methylenedioxymethamphetamine (Ecstasy) Decreases Inflammation and Airway Reactivity in a Murine Model of Asthma

Abstract: Objective: 3,4-Methylenedioxymethamphetamine (MDMA), or ecstasy, is a synthetic drug used recreationally, mainly by young people. It has been suggested that MDMA has a Th cell skewing effect, in which Th1 cell activity is suppressed and Th2 cell activity is increased. Experimental allergic airway inflammation in ovalbumin (OVA)-sensitized rodents is a useful model to study Th2 response; therefore, based on the Th2 skewing effect of MDMA, we studied MDMA in a model of allergic lung inflammation in OVA-sensitize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Airway inflammation induced by ovalbumin (OVA) aerosol challenge in OVA-sensitized animals mimicked some pathological characteristics of asthma, e.g., peribronchial edema and increased number of lymphocytes and eosinophils in the bronchoalveolar lavage fluid (Portela et al, 2001(Portela et al, , 2002. These events were augmented by early-life psychological stress (Chida et al, 2007), unpredictable stressor procedures (Datti et al, 2002), foot shock stress (Portela et al, 2001(Portela et al, , 2002 and chemically-induced stressors Stankevicius et al, 2012;Hamasato et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Airway inflammation induced by ovalbumin (OVA) aerosol challenge in OVA-sensitized animals mimicked some pathological characteristics of asthma, e.g., peribronchial edema and increased number of lymphocytes and eosinophils in the bronchoalveolar lavage fluid (Portela et al, 2001(Portela et al, , 2002. These events were augmented by early-life psychological stress (Chida et al, 2007), unpredictable stressor procedures (Datti et al, 2002), foot shock stress (Portela et al, 2001(Portela et al, , 2002 and chemically-induced stressors Stankevicius et al, 2012;Hamasato et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…During acute inflammation, marked depletion of mast cells due to increases in mast cell activation, and degranulation in the dermis have been detected, and therefore, the inhibition of mast cell activation has been used as a valuable index to predict the efficacy of anti-inflammatory drugs (Cha et al 2013;Yang et al 2013). Apart from the dermis, it has also been reported that increases in mast cells due to migration from nearby connective tissues have been reported in cases of various allergic respiratory disorders (Dahlin et al 2011;Stankevicius et al 2012). Noticeable migration related increase in the mean number of mast cells in the NH 4 OH control mouse of the NH 4 OH exposure coughing mouse model and significant decreases in the mean infiltrating mast cell counts in the ear dermis were observed, which might have resulted from degranulation as demonstrated in the xylene control of the xylene-induced acute inflammatory mouse ear model.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, future work can also assess the relationship of ecstasy to immune function, as immune dysfunction is a precursor to many of the health conditions in this study. Evidence from the animal literature indicates that ecstasy reduces markers of inflammation (Stankevicius et al, 2012); however, human studies on the effects of ecstasy on the immune system have yielded mixed results (Connor et al, 2005;Pacifici et al, 2001Pacifici et al, , 2002Szabo, 2015) and some studies have suggested potential physiological harm associated with ecstasy use (Downey and Loftis, 2014;Halpin et al, 2014;Vegting et al, 2016). Hence, researchers should conduct these investigations prudently as the evidence for this potential pathway remains preliminary.…”
Section: Future Directionsmentioning
confidence: 99%